2014
DOI: 10.1002/clen.201300867
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Uptake and Use Efficiency of Invasive Spartina alterniflora and Native Phragmites australis: Effect of Nitrogen Supply

Abstract: Research ArticleNitrogen Uptake and Use Efficiency of Invasive Spartina alterniflora and Native Phragmites australis: Effect of Nitrogen Supply Plant roots play a vital role in acquisition of resources, while their potential role in plant successful invasions has been largely overlooked. Spartina alterniflora is an invasive grass that has expanded dramatically on the Chinese coast, outcompeting native plant Phragmites australis and resulting in serious negative consequences for invaded ecosystems. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Similarly, to its competitors, knotweed increased the nitrogen concentration in aboveground biomass where more nutrients were available, but it did so to a lesser extent. This finding corroborates evidence from several previous studies that found invaders to possess superior resource-use efficiency (Funk and Vitousek 2007;Shen et al 2011;Osone et al 2014;Ens et al 2015;Qing et al 2015). The ability to maintain a relatively higher nitrogen efficiency when more nitrogen is available-which is equivalent to producing more biomass with the same total amount of nitrogen-may be explained by a higher activity of the enzyme nitrate reductase as found by Chmura et al (2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, to its competitors, knotweed increased the nitrogen concentration in aboveground biomass where more nutrients were available, but it did so to a lesser extent. This finding corroborates evidence from several previous studies that found invaders to possess superior resource-use efficiency (Funk and Vitousek 2007;Shen et al 2011;Osone et al 2014;Ens et al 2015;Qing et al 2015). The ability to maintain a relatively higher nitrogen efficiency when more nitrogen is available-which is equivalent to producing more biomass with the same total amount of nitrogen-may be explained by a higher activity of the enzyme nitrate reductase as found by Chmura et al (2016).…”
Section: Discussionsupporting
confidence: 90%
“…In competition studies, stable isotopes allow researchers to track the partitioning of resources among different individuals or species, and thus to assess the intensity and asymmetry of competition (Kahmen et al 2006). However, so far, stable isotopes have been rarely used to study resource competition between invasive and native plants (but see Littschwager et al 2010;Werner et al 2010;Qing et al 2015;Huangfu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the order of N-uptake rates by four species were inconsistent with their order of total biomass. This lack of association between N-uptake rate and biomass implies that the two invasive species had higher N-use efficiency than the native species, as is common in other invasive plants [34,35]. Higher N-use efficiency rather than faster N-uptake rate appears to be a strategy that enables these invasive species to be more competitive than the natives.…”
Section: Discussionmentioning
confidence: 97%